Antena de ganho aumentado com uma lente de meta-material para aplicações de RFID de longa distância - Moreira, Edmilson Carneiro (2019)
RFID is an Auto Identification and Data Capture (AIDC) system that carries in- formation around using radiofrequency waves that presented a global revenue of 11.2 billion dollars in 2017. Nevertheless, several RFID applications like the automatic identification of cars and trucks in tolls and parking spaces require long-range communication. In those situa- tions, the use of high gain antennas (≥ 9dBi) is a standard solution. Thus, this work propose a novel gain-enhanced microstrip antenna (MSA) with metamaterial planar lens for long-range radio frequency identification (RFID) applications for the 902–928 MHz UHF frequency band. The antenna is a combination of a new general-purpose circularly polarized MSA and a no- vel effective negative refractive index metamaterial (NIM) slab of 25 unit cells, arranged in a 5×5 layout, working as a planar lens for gain enhancement. The general-purpose MSA has an impedance frequency band of 828–1015MHz, a maximum gain of 8.43dBi at 915MHz, an axial ratio frequency band of 896–931MHz, and excellent performance for short and medium range RFID applications. Respectivilly, the new infinite periodicity NIM slab has refractive, electric permittivity, magnetic permeability negative bands of 886–1326MHz, 888–3406MHz and 885–1065MHz. Together, the general-purpose MSA and the NIM planar lens results in the low-cost gain-enhanced antenna for long-range RFID applications, with an 843–993MHz impedance frequency band and a maximum broadside gain enhancement of 48.27%, resulting in a 12.5 dBi gain at 902MHz.